Understanding sperm whale (Physeter macrocephalus) in Pico Island, Azores - Subiron Moreso, Gerard (2021)
Photo-identification has proven a reliable tool to study cetacean species such as the sperm whale (Physeter macrocephalus). Sperm whales have a worldwide distribution that differs between females and males. Females and immature social units are mostly found in tropical and subtropical waters such as the Azores, and males more frequently in higher latitudes. In this study, the use of whale watching as an opportunistic platform to acquire almost year-round data, allowed to assess the sperm whale occurrence, distribution, social structure, and behaviours displayed around Pico Island, Azores during a seven-year period (2012 to 2018). Individuals were photo-identified, and a database of 4851 fluke photographs were visually analysed by three independent researchers, which yielded a sperm whale catalogue for Pico (n = 516). From all catalogued whales, most were sighted only one time in the study period (78%). However, for some individuals it was found a pattern of seasonal residency, with times of individual permanence up to 72 days. Most sightings accounted for females and immature individuals, including calves, which appeared more abundant in summer. Sperm whales off the Azores presented a similar unit size displayed in other regions of the Atlantic Ocean. Male sperm whales, despite the small sample size, were more abundant in summer, and presented different foraging diving times than females. Spatial distribution analysis was performed by calculating the encounter rates for the study area using the sightings and effort. We observed homogeneous distribution, although additional research should be made in some areas. Environmental variables such as depth, distance to coast and sea surface temperature appeared to be a factor influencing the sperm whale occurrence in the area, and more research is needed to provide conclusive answers. Opportunistic platforms such as whale watching, despite some limitations, have proven helpful to obtain cost-efficient and reliable data for research purposes. O cachalote (Physeter ...